PPO.24 The impact of the frequency of fetal ultrasound in the third trimester and the rate of stillbirth in low risk pregnancies. (9th June 2014) - Mone, F; Shrivashankar, M; Ong, S
Abstract : Objectives: To determine if performing fetal growth scans once or twice in the third trimester of pregnancy has an impact on the stillbirth rate in low-risk pregnancies Methods: A retrospective observational study was performed in a tertiary centre. Data was collected using the computerised Northern Ireland Maternity System (NIMATs) on all births and stillbirths in the Royal Maternity Hospital from 2009–2012. We compared pre-2011 versus post 2011 i.e. when patients were scanned twice in the third trimester versus once routinely. Statistical analysis was performed using SPSS Results: There were 18, 856 deliveries in 'low-risk' patients from 2009–2012. The average stillbirth rate in this group was 0.25% per number of low risk pregnancies per annum. The stillbirth rate in the 2009/2010 group was 0.25%. The stillbirth rate in the 2012 group was 0.27%. This difference was not statistically significant [p = 0.897; chi square = 0.017; df =1]. Conclusions: This study indicates that there is no difference in stillbirth rate when a strategy of scanning once or twice in the third trimester of pregnancy is employed in women with an apparent normal pregnancy. A randomised controlled trial is required to determine if routine fetal biometry can reduce stillbirth. This is unlikely to be performed given the large numbers required to perform such a trial which is approximately 250, 000 subjects per arm.